Carbon Capture Adsorbents Based on Ash Residues from the Combustion of Coal with Biomass Blended Fuels - Silviya Boycheva; Boian Mladenov; Ana Borissova; Momtchil Dimitrov; Ivalina Trendafilova; Daniela Kovacheva; Margarita Popova (Energies)
One of the approaches to limit the negative impact on the environment from the burning of coal in the production of heat and electricity is to limit their use by blending them with biomass. Blended fuel combustion leads to the generation of a solid ash residue differing in composition from coal ash, and opportunities for its utilization have not yet been studied. The present paper provides results on the carbon capture potential of adsorbents developed through the alkaline conversion of ash mixtures from the combustion of lignite and biomass from agricultural plants and wood. The raw materials and the obtained adsorbents were studied with respect to the following: their chemical and phase composition based on Atomic Absorption Spectroscopy with Inductively Coupled Plasma (AAS-ICP) and X-ray powder diffraction (XRD), respectively, morphology based on scanning electron spectroscopy (SEM), thermal properties based on thermal analysis (TG and DTG), surface parameters based on N2 physisorption, and the type of metal oxides within the adsorbents based on temperature-programmed reduction (TPR) and UV-VIS spectroscopy. The adsorption capacity toward CO2 was studied in dynamic conditions and the obtained results were compared to those of zeolite-like CO2 adsorbents developed through the utilization of the raw coal ash. It was observed that the adsorbents based on ash of blended fuel have a comparable carbon capture potential with coal fly ash zeolites despite their lower specific surface areas due to their compositional specifics and that they could be successfully applied as adsorbents in post-combustion carbon capture systems.